Association of lymphadenectomy and survival in epithelial ovarian cancer - (:unkn) unknown (MOSBY-ELSEVIER, 2019)
Purpose: Lymph node metastasis has a significant contribution to the prognosis of epithelial ovarian cancer but the role of lymph node dissection in treatment is not clear. In this study, we aimed to retrospectively determine the effect of the number and localization of lymph nodes removed and the number of metastatic lymph nodes on survival. Methods: In this study, we retrospectively reviewed the data of 378 patients (210 patients with lymph node dissection and 168 patients with no dissection) who underwent primary surgery between 2004 and 2014 in various centers with epithelial ovarian cancer diagnosis and followed up in our medical oncology clinic. Demographic and histopathologic features, stage, Ca 125 levels, chemotherapy responses of these patients were examined and survival analyzes were performed. Results: The median age of the patients was 52 years (range 16-89) and median follow-up duration was 39 months (range 1-146). During the analysis, 156 patients (41%) died and 222 patients (59%) were alive. Patients who underwent lymphadenectomy had significantly improved progression free survival (PFS) (18 vs 31 months, P < 0.05) and overall survival (OS) (57 vs 92 months, P < 0.05). OS was longer in patients with > 10 lymph nodes removed compared to patients with 1-10 lymph nodes removed (P = 0.005). Survival was found to be longer in patients with pelvic and paraaortic lymph node dissection compared to patients with only pelvic lymph node dissection (P < 0.05). Patients in stage I-II had no difference in PFS and OS. Patients in stage III-IV had no difference in PFS but there was a significant difference in OS (P=0.02). Conclusion: It may be a therapeutic effect of lymphadenectomy in advanced stage ovarian cancer. The number of lymph nodes removed and the removal of the paraaortic lymph nodes may also contribute to the treatment. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Lymphadenectomy; Ovarian cancer; Survival; Epithelial; SYSTEMATIC LYMPHADENECTOMY; PARAAORTIC LYMPHADENECTOMY; PELVIC LYMPHADENECTOMY; IMPACT; CARCINOMA; RESECTION; SURGERY